Safer Baby Bundle: study protocol for the economic evaluation of a quality improvement initiative to reduce stillbirths. Issue 8 (29th August 2022) - Callander, Emily Joy; Andrews, Christine; Sketcher-Baker, Kirstine; Nicholl, Michael Christopher; Farrell, Tanya; Karger, Shae; Flenady, Vicki
Abstract : Introduction: Stillbirth continues to be a public health concern in high-income countries, and with mixed results from several stillbirth prevention interventions worldwide the need for an effective prevention method is ever present. The Safer Baby Bundle (SBB) proposes five evidence-based care packages shown to reduce stillbirth when implemented individually, and therefore are anticipated to produce significantly better outcomes if grouped together. This protocol describes the planned economic evaluation of the SBB quality improvement initiative in Australia. Methods and analysis: The implementation of the SBB will occur over three state-based health jurisdictions in Australia—New South Wales, Queensland and Victoria, from July 2019 onwards. The intervention is being applied at the state level, with sites opting to participate or not, and no individual woman recruitment. The economic evaluation will be based on a whole-of-population linked administrative dataset, which will include the data of all mothers, and their resultant children, who gave birth between 1 January 2016 and 31 December 2023 in these states, covering the preimplementation and postimplementation time period. The primary health outcome for this economic evaluation is late gestation stillbirths, with the secondary outcomes including but not limited to neonatal death, gestation at birth, mode of birth, admission to special care nursery and neonatal intensive care unit, and physical and mental health conditions for mother and child. Costs associated with all healthcare use from birth to 5 years post partum will be included for all women and children. A cost-effectiveness analysis will be undertaken using a difference-in-difference analysis approach to compare the primary outcome (late gestation stillbirth) and total costs for women before and after the implementation of the bundle. Ethics and dissemination: Ethics approval for the SBB project was provided by the Royal Brisbane & Women's Hospital Human Research Ethics Committee (approval number: HREC/2019/QRBW/47709). Approval for the extraction of data to be used for the economic evaluation was granted by the New South Wales Population and Health Services Research Ethics Committee (approval number: 2020/ETH00684/2020.11), Australian Institute of Health and Welfare Human Research Ethics Committee (approval number: EO2020/4/1167), and Public Health Approval (approval number: PHA 20.00684) was also granted. Dissemination will occur via publication in peer reviewed journals, presentation at clinical and policy-focused conferences and meetings, and through the authors' clinical and policy networks. This study will provide evidence around the cost effectiveness of a quality improvement initiative to prevent stillbirth, identifying the impact on health service use during pregnancy and long-term health service use of children.